Systematic Review: Effectiveness of Self-Efficacy and Audiovisual Education on Diabetic Foot Care - Tanjung, Marina; Liyanovitasari; Arianti, Afrida; Marliana, Dwi; Nur Abdul Hakim, Muhamad; Fitri Anggraeni, Zahra (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder with increasing global prevalence and represents a major public health burden. One of its most serious complications is Diabetic Foot Ulcer (DFU), which significantly contributes to morbidity, reduced quality of life, and lower limb amputation. Poor foot care behavior among patients is commonly associated with insufficient knowledge and low self-efficacy. In recent years, self-efficacy–based education and audiovisual interventions have been introduced as innovative strategies to improve diabetes self-management, particularly foot care practices. This systematic review aims to evaluate the effectiveness of self-efficacy–based and audiovisual educational interventions in improving knowledge, self-efficacy, adherence, and foot care behavior among patients with Type 2 Diabetes Mellitus. This study employed a systematic review design following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Literature searches were conducted in Google Scholar, PubMed, and ScienceDirect databases for studies published between 2015 and 2025. Study quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for quasi-experimental studies. A total of 120 articles were initially identified, 25 duplicates were removed, and after screening and eligibility assessment, 10 studies met the inclusion criteria and were included in the final analysis. Data were synthesized using a narrative approach due to heterogeneity in study designs and measurement tools. Result of this study was all included studies demonstrated statistically significant improvements in at least one outcome variable (p < 0.05). Self-efficacy–based interventions consistently improved patients’ confidence and motivation in performing foot care practices. Audiovisual and digital-based education showed stronger effects in improving knowledge retention, adherence, and behavioral change compared to conventional education methods such as leaflets. Interventions combining education, demonstration, and audiovisual media produced the most comprehensive improvements in knowledge, self-efficacy, and foot care behavior. Variations in effectiveness were influenced by intervention duration, educational methods, and participant characteristics. Conclusion of this study was Self-efficacy–based and audiovisual educational interventions are effective in improving foot care behavior among patients with Type 2 Diabetes Mellitus. These interventions enhance cognitive, psychological, and behavioral outcomes and have the potential to prevent Diabetic Foot Ulcer. Integration of audiovisual and digital health education into routine diabetes care is strongly recommended.